Carboplatin in combination with etoposide for advanced small cell lung cancer complicated with idiopathic interstitial pneumonia: a single-arm phase II study - Masaru Matsumoto; Yuji Minegishi; Katsuyuki Higa; Aya Fukuizumi; Naomi Onda; Susumu Takeuchi; Akihiko Miyanaga; Akihiko Gemma; Masahiro Seike (BMC Pulmonary Medicine)
Abstract Background Acute exacerbation (AEx) of interstitial pneumonia is the most common lethal adverse event related to the pharmacological treatment of patients with lung cancer complicated with interstitial pneumonia. Although small cell lung cancer (SCLC) is linked to poor prognosis, it exhibits good response to chemotherapy. Few previous research studies have investigated the safety and efficacy of treatment for advanced SCLC complicated with idiopathic interstitial pneumonia (IIP). We conducted a single-arm phase II study to evaluate the safety and efficacy of carboplatin plus etoposide for the treatment of patients with SCLC complicated with IIP. Methods Chemotherapy-naïve patients with advanced SCLC complicated with IIP were enrolled. Patients received carboplatin every 21–28 days at a dose of area under the curve 4–6 on day 1 and etoposide at a dose of 80–100 mg/m2 on days 1–3. Results Thirty-one patients were enrolled between December 2009 and December 2022. A median of four cycles of carboplatin plus etoposide were administered. Acute exacerbation of idiopathic interstitial pneumonia was not observed; the rate of AEx was 0% (95% confidence interval [CI]: 0–9.6%, p = 0.038). The objective response rate was 83.9% (95% CI: 82.5–85.2). The median progression-free survival and overall survival were 5.9 (95% CI: 4.7–6.8) months and 14.0 (95% CI: 7.6–27.6) months, respectively. The 1-year survival rate was 61% (95% CI 41–76). Conclusions The carboplatin plus etoposide treatment was tolerable and effective in SCLC patients complicated with IIP.